Analisis Yuridis terhadap Peranan Kepolisian dalam Sistem Peradilan Pidana di Indonesia - Mohd. Yusuf Daeng M.; Shinta Frimayanti; Fajar Rizki; Rahmat Agusman Siddik; Lestari Hulu (Departement of Mathematics Education, 2023)
Abstract The police are one of the law enforcers who have a very important role in the criminal justice system in Indonesia. The role and influence of the police in the criminal justice system will be reviewed from the investigation stage to the investigation, which will then be transferred to the prosecutor's office. The Police and the Prosecutor's Office as the two pillars of law enforcement in the function of investigation and prosecution in addition to Correctional Institutions as executors of crimes under the control of the Government's power. The police can be said to be the initial pillar in the course of a criminal justice system, because the police process is the initial stage of the criminal justice system. This type of research is normative legal research with a case approach, legislation, and analysis. This research will examine the position and important role of the police in the criminal justice system in Indonesia.